THE COMPARATIVE STUDY OF EMOTIONAL SPORTS PROFILE BETWEEN VOLEEYBALL AND TRADITIONAL KARATÊ-DÔ ATHLETES (Fiep Bulletin - online, 2015)
The fact of we need every day  more complete competition athletes make us find some factors that can influence  the performance like psychological factors. In this perspective the study objective was compare emotional profile in sports between volleyball and traditional karatê-dô athletes. The data base was collected in Brazilians Championship in twice modalities, with 59 volleyball athletes and 58 traditional karatê-Dô athletes. The tool used was Inventory of Emotional Sports Profile by TUTKO and TOSI (1976) and adapted version used for individual sports. The ecstatic analyses used was MANOVA, in the p
Keywords: emotional sports profile; athletes; volleyball and traditional karatê-do